AB0078 Effect of Mpges-1 Targeting on Lipid Metabolism in Human Cells. (10th June 2014) - Korotkova, M.; Idborg, H.; Raouf, J.; Ossipova, E.; Checa, A.; Olsson, P.; Leclerc, P.; Oliynyk, G.; Wheelock, C.; Jakobsson, P.-J.
Abstract : Background: Microsomal prostaglandin E synthase-1 (mPGES-1) is the terminal enzyme in the induced PGE2 production and well-recognized target for the development of novel anti-inflammatory drugs. Genetic deletion and inhibition of mPGES-1 appears to be protective in experimental models of arthritis. Targeting mPGES-1 alters eicosanoid profiles and may potentially affect the metabolism of other lipids. Fatty acids (FA) play essential roles as energy substrates, membrane structural components, second messengers and precursors of lipid mediators. Genetic deletion of mPGES-1 resulted in reduced levels of MUFA in the mouse spleen suggesting a decreased activity/expression of stearoyl-CoA-desaturase (SCD). SCD has been implicated in modulation of inflammation. However whether mPGES-1 inhibition affects lipid metabolism in human cells is not known. Objectives: To investigate the effect of mPGES-1 inhibition on lipid metabolism in human cells. Methods: A549 cells were induced with IL-1b and treated with mPGES-1 inhibitor (compound III) or COX-2 inhibitor (NS398). Eicosanoid profiles were analyzed using LC-MS/MS and protein profiles were analyzed using mass spectrometry based proteomics. FA composition of total lipids was determined using gas chromatography with flame ionization detector and sphingolipids were analysed by LC-MS/MS. Results: Prostanoid profiles in supernatants from the IL-1b-induced cells treated with the COX-2 or mPGES-1 inhibitors were significantly different suggesting diverse effects of the inhibitors on down-stream pathways. Proteomic analysis of A549 cells identified the reduction of SCD levels in response to treatment with mPGES-1 or COX-2 inhibitors, as well as the suppression of the levels of a number of proteins involved in metabolism of fatty acids and sphingolipids. Conclusions: The results suggest that down-regulation of COX-2/mPGES-1/PGE2 axis affects the lipid metabolism in A549 cells. These effects have important implications regarding potential consequences of pharmacologic mPGES-1 inhibition. Acknowledgements: The Swedish Research Council, The Swedish Rheumatism Association, King Gustaf V 80 years Foundation, The Swedish Society of Medicine, Karolinska Institutet Foundation, The Swedish County Council and Marianne and Marcus Wallenberg foundation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5002